2013
DOI: 10.2903/j.efsa.2013.3261
|View full text |Cite
|
Sign up to set email alerts
|

Statement on the safety of ‘Cetyl Myristoleate Complex’ as an ingredient in food supplements

Abstract: Following a request from the European Commission, the Panel on Dietetic Products, Nutrition and Allergies was asked to update its opinion on the safety of ‘Cetyl Myristoleate Complex’ (CMC) as a novel food ingredient in the light of a new repeated dose 90‐day oral toxicity study in mice. In its previous opinion of 2010, the Panel concluded that based on the available data, the safety of CMC as an ingredient in food supplements has not been established. This conclusion was based on the considerations that in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The Panel notes the low rate of hydrolysis of the two esters found in a newly provided in vitro hydrolysis study and therefore reiterates the need for adequate safety information on the unhydrolysed esters contained in CMC as expressed in its opinions of and 2013(EFSA NDA Panel, 2010, 2013.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Panel notes the low rate of hydrolysis of the two esters found in a newly provided in vitro hydrolysis study and therefore reiterates the need for adequate safety information on the unhydrolysed esters contained in CMC as expressed in its opinions of and 2013(EFSA NDA Panel, 2010, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the Commission requested EFSA to review and update its opinion by taking into account a report of a new subchronic 90-day oral toxicity study conducted with -Cetylated Fatty Acid Esters Powder 50 %‖ (Cetyl Myristoleate Complex, CMC) in mice (CMC Study Report, 2012). In 2013, the NDA Panel noted that the new 90-day study and its report have many shortcomings, and considered that this study cannot serve as a reliable source of information supporting the absence of adverse effects of CMC (EFSA, 2013). The Panel also noted that apart from information on the safety of the hydrolysis moieties, and in the absence of sufficient data with respect to kinetics of hydrolysis, adequate safety information on the parent compounds of CMC remains relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No ADME studies were provided for the NF or with other cetylated fatty acids. The applicant referred to the ADME on triglycerides, fatty acids and the EFSA Opinions on another, similar NF application ('CMC') (EFSA NDA Panel, 2010, 2013.…”
Section: Absorption Distribution Metabolism and Excretion (Adme)mentioning
confidence: 99%
“…In terms of use in foods, the safety of cetyl myristoleate complex, a specific CFA formulation comprising 50% CFAs, 48% corn starch, and 2% silicon dioxide, for use as a novel food has been previously reviewed by the European Food Safety Authority (EFSA, 2010(EFSA, , 2013(EFSA, , 2014. During the course of these risk assessments, EFSA concluded that the data presented were insufficient to support the safety in foods.…”
mentioning
confidence: 99%